The Role Of Tapal Kuda Television Journalists Association In Transforming University Students Into Competent Journalists - Nilu Dian Apriliana; Muhammad Iqbal (Journal of Communication Studies, 2026)
This study aims to analyze the communication strategies implemented by the Tapal Kuda Jember Television Journalists Association in presenting local television news content. The background of this study stems from the need for journalist organizations to adapt amid the dynamics of media digitalization, audience fragmentation, and demands for journalistic professionalism. The strategic organizational communication approach is used as a theoretical basis to understand how organizational structures, communication channels, and feedback mechanisms are built to achieve the goal of presenting informative and relevant news to the local public. The research method used a qualitative descriptive design with data collection techniques in the form of in-depth interviews, observation of organizational activities, and analysis of internal documentation. The results of the study show that the communication strategy of IJTI Tapal Kuda Jember includes vertical, horizontal, and collaborative communication patterns among its members to ensure consistency in news presentation, strengthen journalistic professionalism, and preserve local identity in content production. Internal evaluation mechanisms and routine coordination were also found to play a role in improving the effectiveness of information dissemination and editorial decision-making. This study concludes that the organizational communication strategy implemented by IJTI Tapal Kuda Jember has a direct impact on the quality and character of local television news. These findings contribute theoretically to the study of strategic organizational communication and offer practical recommendations for journalist associations and local television stations in improving coordination, content quality, and media sustainability at the regional level.